Effects of a multiprofessional program of obesity treatment and its cessation on physical fitness related to health in adolescents - doi: 10.4025/reveducfis.v23i3.14855 - Silva, Danilo Fernandes da (2012)
The aim of the study was to evaluate the effects of a multiprofessional program of obesity treatment (PMTO) and its cessation on physical fitness and body composition in adolescents. We conducted a quasi-experimental study with 19 overweight/obese adolescents of both gender and aged from 10 to 18 years. These adolescents participated in a 16 weeks of intervention focused on change food and exercise behavior. After that, the adolescents returned to evaluation after eight weeks of activities cessation. We observed important changes related to cardiorespiratory fitness (26,39±6,18ml/kg/min to 30,99±7,84ml/kg/min) and body fat (40,67±6,61% to 36,73±7,77%) but changes were not maintained after cessation period (27,56±7,31ml/kg/min and 38,09±7,84%, respectively). The results showed 16 weeks of PMTO were enough to improve the physical fitness and body composition, however, did not change lifestyle in these adolescents in order to maintain the gains promoted by PMTO.